Quantifying Long-Term Retention of Excised Fat Grafts: A Longitudinal, Retrospective Cohort Study of 108 Patients Followed for Up to 8.4 Years. Issue 5 (May 2017) - Herly, Mikkel; Ørholt, Mathias; Glovinski, Peter V.; Pipper, Christian B.; Broholm, Helle; Poulsgaard, Lars; Fugleholm, Kåre; Thomsen, Carsten; Drzewiecki, Krzysztof T.
Abstract : Background: Predicting the degree of fat graft retention is essential when planning reconstruction or augmentation with free fat grafting. Most surgeons observe volume loss over time after fat grafting; however, the portion lost to resorption after surgery is still poorly defined, and the time to reach steady state is unknown. Methods: The authors compiled a retrospective, longitudinal cohort of patients with vestibular schwannoma who had undergone ablative surgery and reconstruction with excised fat between the years 2006 and 2015. Fat volume retention was quantified by computed tomography and magnetic resonance imaging and used to model a graft retention trajectory and determine the volumetric steady state. In addition, the authors evaluated the association between graft retention and secondary characteristics, such as sex and transplant volume. Results: A total of 108 patients were included. The average baseline graft volume was 18.1 ± 4.8 ml. The average time to reach steady state was 806 days after transplantation. By this time, the average fat graft retention was 50.6 percent (95 percent CI, 46.4 to 54.7 percent). No statistically significant association was found between baseline graft volume and retention. Fat graft retention over time was significantly higher in men than in women (57.7 percent versus 44.5 percent; p < 0.001). Conclusions: The authors' data provide evidence that the time to reach fat graft volumetric steady state is considerably longer than previously expected. Fat grafts continue to shrink long after the initial hypoxia-induced tissue necrosis has been cleared, thus indicating that factors other than blood supply may be more influential for fat graft retention. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.